2021
DOI: 10.1016/j.fertnstert.2021.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal outcomes of pregnancies resulting from assisted reproduction technology in SARS-CoV-2-infected women: a prospective observational study

Abstract: Objective To evaluate the perinatal and maternal outcomes of pregnancies in SARS-CoV-2 infected women, comparing spontaneous and In Vitro Fertilization (IVF) pregnancies (with either own or donor oocytes). Design Multicentre, prospective, observational study. Setting 78 centres participating in the Spanish COVID19 Registry. Patients 1,347 SARS-CoV-2 positive pregnant women registered consecutively between February … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…They noted a higher incidence of preeclampsia and ICU admission in these women compared to naturally conceived women with other maternal and neonatal outcomes being similar. [ 27 ] Recently, the ESHRE working group collected data from 80 cases from 32 countries from May 20 to June 21 and noted that medically assisted pregnancies are not differentially affected by COVID-19 infection compared to spontaneous pregnancies and that performing ART with due precautions and triaging can be advocated. [ 18 ]…”
Section: Discussionmentioning
confidence: 99%
“…They noted a higher incidence of preeclampsia and ICU admission in these women compared to naturally conceived women with other maternal and neonatal outcomes being similar. [ 27 ] Recently, the ESHRE working group collected data from 80 cases from 32 countries from May 20 to June 21 and noted that medically assisted pregnancies are not differentially affected by COVID-19 infection compared to spontaneous pregnancies and that performing ART with due precautions and triaging can be advocated. [ 18 ]…”
Section: Discussionmentioning
confidence: 99%
“…In our dataset, C-section was reported for 61.1% of the deliveries. While these figures are higher than general Caesarean delivery rates, it is possible that concerns about transmission of the infection and potential deterioration of maternal status during labour have led to an increase in C-sections ( Engels Calvo et al , 2021 ). Other possible explanations for the high rate of C-sections are physicians having a lower threshold for C-section for MAR pregnancies or random variation in this small sample.…”
Section: Discussionmentioning
confidence: 99%
“…A multicentric observational study evaluated totally 1347 SARS-CoV-2-infected pregnant women: 1273 spontaneous pregnancies and 74 IVF pregnancies. This study reported that hight ICU admittance rate of IVF pregnancies was because of preeclampsia but not to fertilization type suggesting that preeclampsia was caused by SARS-CoV-2 infection but not because of conception method [ 60 ].…”
Section: Is There a Correlation Between Severe Acute Respiratory Synd...mentioning
confidence: 99%